Real waiting times for surgery. Proposal for an improved system for their management - Ignacio Abásolo; Patricia Barber; Beatriz González López-Valcárcel; Octavio Jiménez (Elsevier, 2014)
Objectives: In Spain, official information on waiting times for surgery is based on the interval between the indication for surgery and its performance. We aimed to estimate total waiting times for surgical procedures, including outpatient visits and diagnostic tests prior to surgery. In addition, we propose an alternative system to manage total waiting times that reduces variability and maximum waiting times without increasing the use of health care resources. This system is illustrated by three surgical procedures: cholecystectomy, carpal tunnel release and inguinal/femoral hernia repair. Methods: Using data from two Autonomous Communities, we adjusted, through simulation, a theoretical distribution of the total waiting time assuming independence of the waiting times of each stage of the clinical procedure. We show an alternative system in which the waiting time for the second consultation is established according to the time previously waited for the first consultation. Results: Average total waiting times for cholecystectomy, carpal tunnel release and inguinal/femoral hernia repair were 331, 355 and 137 days, respectively (official data are 83, 68 and 73 days, respectively). Using different negative correlations between waiting times for subsequent consultations would reduce maximum waiting times by between 2% and 15% and substantially reduce heterogeneity among patients, without generating higher resource use. Conclusion: Total waiting times are between two and five times higher than those officially published. The relationship between the waiting times at each stage of the medical procedure may be used to decrease variability and maximum waiting times.